(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article explores effective methodologies for teaching Russian to students of technical and vocational colleges. It emphasizes the importance of integrating practical and professional contexts into language instruction to enhance students’ communicative competence. The study analyzes various teaching approaches, including interactive lessons, multimedia resources, online platforms, and mobile applications, highlighting their role in developing listening, speaking, reading, and writing skills. Particular attention is given to strategies that increase student motivation, support personalized learning, and foster active participation. The article concludes that combining traditional teaching methods with modern technological tools creates a more engaging, effective, and learner-centered environment, improving overall language proficiency and preparing students for professional communication in technical and vocational settings.